As-built inspection for concrete tank using non-contact three dimensional data acquisition / Nurul Huda Abd Rahman - Abd Rahman, Nurul Huda (2019)
Three dimensional laser scanner is a powerful data collection system that provides 3D information for a specific area of interest. It is the predominate technology for terrestrial survey, construction and as-built analysis. TLS commonly produce centimeter spatial and range accuracy at several hundred meter range. Due to tank inspection that require accurate data, TLS is able to provide high accuracy data for tank inspection requirement. Several approaches tank inspection method has been done by previous research. It has shows have limitation in data acquisition, data processing and data analysis. Therefore, the aim of this study is to investigate the suitability of TLS measurement technique in concrete tank inspection. In order to achieve the objective, some analysis has been done through the methodology by perform dimensional analysis and point to point analysis. There are 42 artificial targets distributed of concrete tank are used in this analysis to examine data quality of TLS in concrete tank inspection by total station data as benchmarking. Second analysis is to investigate the reliability of TLS data to perform surface inspection by create surface deviation model to detect defect surface on concrete tank. The result was evaluated by standard deviation, RMS residuals and surface deviation model. The result has shows TLS data can be used on concrete tank inspection.